Winning Marriage : The Inside Story Of How Same-Sex Couples Took On The Politicians And Pundits -- And Won - Solomon, Marc, 1966- (ForeEdge, 2014)
Ten years ago no state allowed same-sex couples to marry, support for gay marriage nationwide hovered around 30 percent, and politicians everywhere thought of it as the third rail of American politics -- draw near at your peril. Today, same-sex couples can marry in seventeen states, polls consistently show majority support, and nearly three-quarters of Americans believe legalization is inevitable. In Winning Marriage Marc Solomon, a veteran leader in the movement for marriage equality, gives the reader a seat at the strategy-setting and decision-making table in the campaign to win and protect the freedom to marry. With depth and grace he reveals the inner workings of the advocacy movement that has championed and protected advances won in legislative, court, and electoral battles over the decade since the landmark Massachusetts ruling guaranteeing marriage for same-sex couples for the first time. From the gritty battles in the state legislatures of Massachusetts and New York to the devastating loss at the ballot box in California in 2008 and subsequent ballot wins in 2012 to the joyous victories of securing President Obama's support and prevailing in the Supreme Court, Marc Solomon has been at the center of one of the great civil and human rights movements of our time. Winning Marriage recounts the struggle with some of the world's most powerful forces -- the Catholic hierarchy, the religious right, and cynical ultraconservative political operatives -- and the movement's eventual triumph.